LANDASAN RELIGIUS PENDIDIKAN DAN PEMBELAJARAN - Rachmadian Choirunnisa; Habib Anwar Al Anshori (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article discusses the religious foundations of education and learning as a fundamental basis for shaping students character, morality, and spirituality. Religious foundations play an important role in directing educational processes so that they are not only oriented toward cognitive aspects, but also toward the development of faith, moral values, and social ethics. This study employs a qualitative approach using a literature review method through the analysis of various relevant references concerning religious value-based education. The findings indicate that the implementation of religious foundations in education can create a humane, moral, and personality-oriented learning environment. Furthermore, the integration of religious values into the learning process can enhance students’ spiritual awareness, strengthen attitudes of tolerance, discipline, and responsibility, and build harmonious relationships between teachers and students. Therefore, religious foundations should become an integral part of the educational system in addressing the challenges of modernization and moral crises in contemporary society.